Enzensberger's challenge to leftist communicologists - Eric Louw (Communicare)
In his work on the media, Hans Enzensberger challenges many of the traditional assumptions of the Left. These challenges form the sub stance of this essay. Importantly, Enzensberger was not content with merely attacking the (Marxist-domi nated) Left Rather, he simulta neously proposed an 'alternative' left-wing communication theory. His proposed "praxis" theory  of com munication and related demand for democratic participatory media structures are examined with some reference to their adoptability in South Africa. The Enzensbergian challenge, how ever, has implications not only for left communicologists, but for com- munication studies in general. This is because he raises important issues for political communication such as the relationship of the media to democracy; of access to the media; and of media manipula tion; etcetera.